The "flowerpot" sign: Inference of poor renal function in high grade vesicoureteral reflux by calyceal orientation. Issue 1 (February 2015) - Martin, Aaron D.; Gupta, Kavita; Swords, Kelly A.; Belman, A. Barry; Majd, Massoud; Rushton, H. Gil; Pohl, Hans G.
Summary: Introduction/objective: Modern radiographic advances have allowed for detailed and accurate imaging of not only urologic anatomy but also urologic function. The art of observational inference of subtle anatomic features and function from a static radiograph is being traded for new, more precise, and more expensive modalities. While the superiority of these methods cannot be denied, the total information provided in simpler tests should not be ignored. The relationship between high grade vesicoureteral reflux with the dilated calyces arranged cephalad to a dilated funnel-shaped renal pelvis on VCUG and reduced differential renal function has not been previously described, but has been anecdotally designated a "flowerpot" sign by our clinicians. We hypothesize that the appearance of a "flowerpot" kidney as described herein is an indicator of poor renal function in the setting of high grade VUR. Study design: IRB approval was obtained and 315 patients were identified from system-wide VCUG reports from 2004–2012 with diagnosed "high grade" or "severe" vesicoureteral reflux. Inclusion into the study required grade IV or V VUR on initial VCUG and an initial radionuclide study for determination of differential function. Patients with a solitary kidney, posterior urethral valve, multicystic dysplastic kidney, renal ectopia, or duplex collecting systems were excluded. Grade of reflux, angle of the inferior-superior calyceal axis relative to the lumbar spine, and differential uptake were recorded along with presence of the new "flowerpot" sign. Variables were analyzed using the Mann–Whitney U test to determine statistical significance. Results: Fifty seven patients met inclusion criteria with 11 being designated as "flowerpot" kidneys. These "flowerpot" kidneys could be objectively differentiated from other kidneys with grade IV and/or grade V VUR both by inferior–superior calyceal axis (median angle, 52° [37–66] vs. 13° [2–37], respectively p < 0.001) and by differential renal uptake (median, 23% [5–49] vs. 45% [15–81], respectively p < 0.001). Likewise, there was no difference between either calyceal axis (median angle, 13° [3–20] vs. 13° [2–37]) or differential function (median, 48% [24–81] vs. 40% [15–66], p = 0.129) when comparing kidneys with grade IV and grade V VUR, respectively, that did not demonstrate the "flowerpot" sign. Discussion/conclusion: Grading of VUR is used to provide a common language for scientific discussion and determine prognosis for children with similar attributes. The dysmorphic calyceal system in the "flowerpot" kidneys supports the theory of abnormal renal blastema induction associated with abnormal differentiation of the ureteral bud. Even in the absence of urinary tract infections and/or pyelonephritis, renal abnormalities and decreased differential function can be observed on renal scintigraphy. This study also confirms the male predominance and functional similarities between grade 4 and 5 refluxing renal units. Recognizing this is a limited observational study based on imaging alone, the "flowerpot" sign is an indicator of the most severe form of grade 5 VUR but is only one factor in predicting long term overall renal prognosis. However, 14% (8/57) of our cohort had a relative uptake of less than 20% with 5 of these exhibiting the "flowerpot" sign. The "flowerpot" sign on VCUG can be used as indirect evidence of poor differential renal function and, therefore, useful in guiding parental expectations prior to formal functional imaging.